ON PRIMITIVE Zp-ALGEBRA - Ameer Jaber (Boletim da Sociedade Paranaense de Matemática, 2018)
Our main purpose is to provide for primitive associative Zp-algebras a structure theory analogous to that for algebras and superalgebras [1, 7, 8, 9, 10] and to classify primitive Zp-rings having a minimal one sided Zp-ideal.